Combining real-time fluorescence spectroscopy and flow cytometry to reveal new insights in DOC and cell characterization of drinking water - Schuster, Jonas; Huber, Johanna; Stumme, Jakob; Grieb, Anissa; Ernst, Mathias (Frontiers in Environmental Chemistry, 2022)
Sudden changes in the drinking water quality can cause harmful consequences for end users. Thus, real-time monitoring of drinking water quality can serve as early-warning and give crucial gains for securing safe water distribution. The advantages of simultaneous real-time measuring of flow cytometry and fluorescence spectroscopy was investigated. A contamination event by spiking drinking water samples with organic nutrients was investigated in a lab scale analysis. The flow cytometric data was analyzed by creating fingerprints based on differentiation into high and low nucleic acid cells (HNA/LNA). A detailed characterization of these showed that the increase of HNA cells indicate an increase in the bacterial growth potential even before the actual TCC increases. The fluorescence data was decomposed via PARAFAC method, which revealed seven fluorescent components. Three components (all aromatic protein-like) were identified as considerable concerning the microbiological condition of drinking water cells: components 4 (λEx = 279 nm, λEm = 351 nm), 6 (λEx =279 nm, λEm = 332 nm) and 7 (λEx = 276 nm, λEm = 302 nm). Component 6 was proven as a possible organic variable for an appropriate monitoring of the TCC, whereas components 4 and 7 were identified as organic compounds which represent nutrients for drinking water microorganisms. Overall, combining both methods for real-time monitoring can be a powerful tool to warrant drinking water quality.